The impact of coaches` ethical leadership behaviour on athletes` voice and performance: The role of accountability - White, S.; Rezania, D. (Sport, Business and Management, 2020)
Purpose: Ethics and leadership are ongoing topics in high performance sports. The purpose of this paper is to provide an insight into the relationship between coaches` ethical leadership behaviour, as perceived by athletes, and its impact on student-athlete accountability, voice and performance. Design/methodology/approach: The paper examines the constructs of coaches` ethical leadership behaviour, felt accountability and voice behaviour. The authors surveyed student-athletes from a variety of sports who compete in the Ontario University Athletics Regional Association. A total of 303 respondents (n=303) completed the survey. Partial least squares path modelling algorithm was utilised for testing hypotheses. Findings: The results of the study indicate a significant relationship between a coach exhibiting ethical leadership behaviour and student-athlete voice behaviour and performance. Felt accountability mediates the effect of ethical leadership on voice and performance. Practical implications: This study provides support for the hypothesis that coaches who behave ethically and whose actions represent their words create an environment where a student-athlete feels accountable. This is a powerful concept as it can positively impact individual and team success. The findings suggest that one of the ways that coaches can impact athletes` performance is to demonstrate and model ethical conduct, and reward ethical acts. Originality/value: The paper examines how coaches` ethical behaviour might impact individual processes of accountability, voice and performance. Second, the paper uses the construct of accountability to explain how coaches` ethical leadership impacts student-athlete behaviour. The accountability literature indicates that followers` behaviours can be understood as the consequences of his/her perceived accountability towards the leader.